Can Fullerene Analogues be the Carriers of the Diffuse Interstellar Bands?. Issue Volume 9:Issue S297(2013) (21st February 2014) - Cami, J.
Abstract: Fullerenes and their derivatives are amongst the most stable carbonaceous species known and have therefore been proposed as ideal candidates to carry some of the diffuse interstellar bands (DIBs). Evidence for these species in space first came from a few DIBs that have been tentatively identified with electronic transitions of C60 + ; in recent years, infrared observations have furthermore revealed fullerenes in a variety of circumstellar and interstellar environments. With the presence of the fullerene family in space established, we review what is known about cosmic fullerenes and their derivatives and what role they could play as potential DIB carriers.